“Peer Teaching Strategy To Increase Mathematics Proficiency Level” (An Action Research) (Eastern Samar State University) (International Journal of Scientific Research and Management (IJSRM), 2018)
Peer Teaching/tutoring is used as school-based intervention that has been shown to improve academic skills, generate development of appropriate social skills, and enhance peer relations for both tutees and tutors. The purpose of this study was to determine the effectiveness of the implementation of a peer teaching/tutoring program in mathematics on the academic achievement level of Grade 3 pupils in Lupok Central School. This study aimed to analyse peer teaching as an intervention strategy that will increase the performance among Grade 3 Mathematics pupils at Lupok Central School, Guiuan North District, Guiuan Eastern Samar through the 1st and 4th Grading periods of School Year 2017 - 2018. Specifically, it sought to answer the following questions: • What is the Mean Percentage Score (MPS) in Mathematics of Grade 3 Pupils in Lupok Central School at the beginning of 1st Grading of School Year 2017 – 2018 before peer teaching intervention? • What is the Mean Percentage Score in Mathematics of Grade 3 Pupils in Lupok Central School at the end of 4th Grading of School Year 2017 – 2018 after peer teaching intervention? • Is there a Significant difference before and after the intervention program? • What intervention program may be proposed based on the findings of the study? Based on the data gathered/collected from the class adviser of Grade 3 Section Bougainvillea in Lupok Central School, the result of base line MPS from 1st Grading period specifically in mathematics subject is 74.22 which is considered below the 75% proficiency level. The result showed a radical increase in Mean Percentage Score in mathematics subject after the intervention was given to the Grade 3 pupils with the previous result of 74.22% from the 1st Grading into 82.11% MPS result in the 4th Grading period. The results of the study further revealed that the implementation of Peer teaching strategy has a positive effect in increasing the academic performance in mathematics of Grade 3 pupils. There was 7.89% increase in MPS for mathematics subject from the first grading to the fourth grading period.